Increased Levels of Diadenosine Polyphosphates in Dry Eye - Peral, Assumpta; Carracedo, Gonzalo; Acosta, M. Carmen; Gallar, Juana; Pintor, Jesus (Investigative ophthalmology & visual science, 2006)
To analyze the levels of the diadenosine polyphosphates Ap4A and Ap5A in tears, in a set of control subjects and in groups of symptomatic and nonsymptomatic persons with dry eye. Ninety-seven subjects participated in the study. The subjects were divided into five experimental groups: control subjects; symptomatic patients with normal tear secretion; symptomatic patients with low tear secretion; forced blink; and corneal mechanical stimulation provided by a gas esthesiometer. The Schirmer I test was used to measure and collect tear secretions from each subject. All samples were processed by high pressure liquid chromatography (HPLC) and their Ap4A and Ap5A levels determined. The levels of Ap4A and Ap5A in tears were greater in all symptomatic patients than in control subjects, especially in symptomatic subjects with low tear secretion. Within the symptomatic subjects with normal tear secretion, significant differences in concentrations of Ap4A and Ap5A were found between men and women. In the forced blink experiments, concentrations of the Ap4A and Ap5A rose with increasing blink frequency. When the cornea was mechanically stimulated, the levels of Ap4A and Ap5A rose significantly during both moderate and high-flow rate tests. The increased levels of Ap4A and Ap5A in tears of patients with dry eye allow these dinucleotides to be used as objective biomarkers in dry eye conditions.